National Corporate University of ASN: Orchestrating Strategic Competency Development at the National Level - Savira, Evi Maya; Savitri, Renny; Ahad, Madya Putra Yaumil (KnE Social Sciences, 2022)
State Owned Enterprises (SOEs) have inspired the National Institute of Public Administration in designing and creating a corporate university for national civil service – the National Corporate University of ASN. This corporate university aims to accelerate the development of civil service competencies in line with national development goals. This university is different from general corporate universities that have been implemented in several government agencies as well as SOEs. Although details about the corporate university have been disseminated several times across various stakeholders, there are still misinterpretations regarding on it. This paper explains the urgency of having such a corporate university as an instrument in orchestrating the national strategy through competency development. A descriptive qualitative apprach was used and data were collected through discussions with experts and corporate practitioners, and through reviewing the literature related to the concept of corporate universities. It was found that the scope of this corporate university includes: National leadership development programs, cross-agency strategic competency development programs, and knowledge management and learning management systems that support implementation. The results of this study will be used as a reference in subjects related to corporate universities as well as for policy recommendations for corporate university practitioners. Keywords: corporate university, National Corporate University of ASN, competency development